Keto Acids as Growth-limiting Factors in Autotrophic Growth of Thiobacillus thiooxidans - Borichewski, R. M. (1967)
When the strictly autotrophic bacterium Thiobacillus thiooxidans was grown on sulfur, keto acids accumulated in the medium until they reached an inhibitory level at which growth ceased. Much greater growth was possible if these substances were continually dialyzed out of the medium.